The Civil Service Law System in Poland – Selected Issues - Drobny, Wojciech (Public Governance, Administration and Finances Law Review, 2018)
The article refers to the topic of civil service law in Poland. It describes the organization of civil service system in comparison to other international solutions and it gives the historical background of how it has been evolving so far. Particularly it refers to the elements of its regime, the position and duties of the Polish Head of the Civil Service and rights and duties of the civil service corpus’ members. The author claims that the changes taking place in the area of this part of law are due to the domination of private law (labor law) over public law (administrative law). This tendency currently prevails in the western legislation.